Uterine primitive neuroectodermal tumor: a case report - Celik, Husnu; Gurates, Bilgin; Karaoglu, Aziz; Yavuz, Adem; Dagli, Ferda; Ozercan, Resat (Springer Heidelberg, 2009)
Primitive neuroectodermal tumors of uterus (PNET) are extremely rare in tumors of the female genital system and therefore there is no sufficient information about their diagnosis, treatment, and follow-up. The case is a 32-year-old, operated in emergency conditions due to intra-abdominal hemorrhage, and discusses our diagnosis and treatment approaches in the light of literature data. To the best of our knowledge, this is first report of uterine PNET that presented with intraabdominal hemorrhage due to uterine rupture. Despite advances in therapy, the prognosis is poor. The low number of these cases precludes accurate standardization of therapy.
Keywords: Primitive neuroectodermal tumors; Uterus; PNET